Smart parking: An efficient approach to city’s smart management and air pollution reduction - Seyed Jalalaldin Faraji; Marjan Jafari Naozar (Journal of Air Pollution and Health, 2019)
Introduction: Due to increasing the population of cities and the physical-spatial expansion of the cities, vehicles are being used progressively, which has caused many problems for the cities including traffic increase, chaos in finding urban parking lots, increase of environmental pollution, decrease of citizens’ satisfaction, and so on. Among the many urban problems, parking lot is one of the issues that has been heavily debated in recent years. The lack of sufficient number of parking lots, on the one hand, and the related disorder and management problems, on the other hand, have led to a range of managerial and environmental problems. Meanwhile, one of the paradigms that has focused on this issue in recent years is smart city paradigm, which has offered the smart parking. This paradigm believes that parking, as a part of the city’s space, can be smart and can help urban management. Materials and methods: This is an applied research in terms of purpose and a descriptive-analytical research in terms of nature. The required data were collected using documentary and field studies and SWOT method was used to analyze the data. Results: This study was conducted to evaluate and investigate the role of smart parking in increasing the efficiency of urban management and its impact on reducing air pollution. Conclusion: Finally, the conclusion of the research have led to key strategies for achieving the research goal.